Kreativitas Guru dalam Proses Belajar Mengajar Mata Pelajaran Akidah Akhlak Pada Kurikulum Merdeka - M Febi Wennisgo; M. Asep Fathur Rozi (Journal on Education, 2024)
The subject of Islamic faith and morality significantly influences students' awareness in behavior and socialization in daily life. Therefore, I conducted research on the creativity of teachers in conducting the teaching and learning process focused on Islamic faith and morality, which is currently using the independent curriculum located at SDI Plus Imam Muslim Kediri. The objectives of this research are: (1) To explain the methods and strategies of teachers in the teaching and learning process of Islamic faith and morality subjects in the independent curriculum at SDI Plus Imam Muslim Kediri. (2) To delineate the supporting and inhibiting factors experienced by teachers in teaching Islamic faith and morality subjects in the independent curriculum at SDI Plus Imam Muslim Kediri. The findings of the research indicate that: (1) Teachers employ various teaching methods for Islamic faith and morality subjects, taking into account the students' needs and classroom situations. They adopt various methods to keep the learning process engaging. (2) Teacher creativity is reflected in the application of expository teaching strategies in teaching and learning activities for Islamic faith and morality subjects. (3) Comprehensive support from all school components is a supportive factor in this learning process. However, there are several factors that may hinder it, such as pressure to adhere to a rigid curriculum, limitations in time and space for designing engaging activities, and a lack of motivation or support from the school environment.